Delirio e neuroscienze - Fargnoli, Francesco (Il sogno della farfalla, 2020)
In recent decades neuroscience research has made considerable progress in the attempt to redefine psychopathology within a pathophysiological framework. However, this type of approach carried out through a reductionist methodology is likely to fail as it is not able to grasp the complexity of its object of research : the human mind. In this article the author proposes the possibility to integrate neuroscientific investigation together with a research on the non conscious dimension in order to comprehend the origin of delusion.